2002
DOI: 10.1046/j.1528-1157.43.s.5.17.x
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Absence Epilepsy Rat from Strasbourg (GAERS), a Rat Model of Absence Epilepsy: Computer Modeling and Differential Gene Expression

Abstract: Summary:Purpose: We present results obtained by computer modeling of the thalamic network and differential gene expression analysis in a rat strain with absence epilepsy, the genetic absence epilepsy rat from Strasbourg (GAERS).Methods: (a) Computer modeling used equations from the Hodgking-Huxley model with a circuit of 13 reticular thalamic (nRt) and 39 thalamocortical (TC) neurons; (b) geneexpression analysis using differential mRNA display (DD), in situ hybridization, Northern blotting, and competitive rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In GAERS an increase of T-type Ca 2+ current in reticular thalamic nucleus neurons has been reported (Tsakiridou et al, 1995) and later on also alterations in Ca v 3.1 and Ca v 3.2 expression in the adult ventroposterior thalamic nuclei and reticular thalamic nucleus neurons, respectively (Talley et al, 2000). Astonishingly, de Borman et al (1999) and Lakaye et al (2002) detected a significant reduction of Ca v 2.3 transcript levels in both cerebellum and medulla of GAERS, two extrathalamocortical brain structures, the brainstem and cerebellum which project to the thalamocortical circuitry, capable of modifying its oscillatory behavior (Filakovszky et al, 1999;Deransart et al, 2001). On the other hand, the WAG/Rij rat model of absence epilepsy was also reported to exhibit altered VGCC expression.…”
Section: Ca V 23 In Non-convulsive Seizures-functional Interdependenmentioning
confidence: 91%
See 1 more Smart Citation
“…In GAERS an increase of T-type Ca 2+ current in reticular thalamic nucleus neurons has been reported (Tsakiridou et al, 1995) and later on also alterations in Ca v 3.1 and Ca v 3.2 expression in the adult ventroposterior thalamic nuclei and reticular thalamic nucleus neurons, respectively (Talley et al, 2000). Astonishingly, de Borman et al (1999) and Lakaye et al (2002) detected a significant reduction of Ca v 2.3 transcript levels in both cerebellum and medulla of GAERS, two extrathalamocortical brain structures, the brainstem and cerebellum which project to the thalamocortical circuitry, capable of modifying its oscillatory behavior (Filakovszky et al, 1999;Deransart et al, 2001). On the other hand, the WAG/Rij rat model of absence epilepsy was also reported to exhibit altered VGCC expression.…”
Section: Ca V 23 In Non-convulsive Seizures-functional Interdependenmentioning
confidence: 91%
“…Furthermore, various extrathalamocortical structures such as the reticular formation, laterodorsal tegmental nucleus, pedunculopontine tegmental nucleus, raphe nuclei, locus coeruleus, basal nucleus of Meynert as well as cerebellar structures project to that circuitry. Some brain structures like hippocampus or cerebellum classically not known to be involved in the production of absence spike-wave discharges could in fact participate in the development of this phenotype (Lakaye et al, 2002). Pathophysiologically, aberrant corticothalamic rhythms are believed to be the substrate of spike-wave discharges.…”
Section: Ca V 23 In Non-convulsive Seizures-functional Interdependenmentioning
confidence: 99%
“…Experimental studies of genetic rat models of absence epilepsy have indicated that the perioral region of the somatosensory (parietal) cortex initiates the seizure activity that entrains the thalamo-cortical circuit and produces generalized SWD activity (Meeren et al, 2002;Polack et al, 2007). No structural changes were observed in SWD generator brain regions, but several changes at the subcellular level have been observed, such as changes in receptor subunits (Beyer et al, 2008;van de Bovenkamp-Janssen et al, 2006) and ion channel expression (de Borman et al, 1999;Klein et al, 2004;Kole et al, 2007;Lakaye et al, 2002;van de Bovenkamp-Janssen et al, 2004;Weiergräber et al, 2008). Recently, a proteomics study identified ATP synthase subunit delta, 14-3-3 zeta isoform, myelin basic protein and macrophage migration inhibitory factor as differentially expressed proteins in these regions in Genetic Absence Epilepsy Rats from Strasbourg (GAERS) (Danis et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…the reticular formation, the pedunculopontine tegmental nucleus, the laterodorsal tegmental nucleus, the basal nucleus of Meynert, the raphe nuclei, the locus coeruleus and cerebellar structures are functionally connected to the TC circuitry. Interestingly, brain structures like hippocampus or cerebellum that are classically not known to be involved in the generation of absence SWDs in fact also participate in the development of the absence epilepsy phenotype [213]. On the pathophysiological level, TC dysrhythmia is assumed to be the substrate of SWDs.…”
Section: Structure Function and Pharmacology Of Voltage-gated Ca2+ Cmentioning
confidence: 99%
“…[222] and Lakaye et al . [213] described a prominent decrease of Ca v 2.3 VGCC in two extrathalamocortical brain structures in GAERS, the brainstem and the cerebellum both of which project to the TC circuitry, capable of modulating its oscillatory activity [227-229]. In addition, the WAG/Rij rat model of absence epilepsy displays altered VGCC expression as well.…”
Section: Structure Function and Pharmacology Of Voltage-gated Ca2+ Cmentioning
confidence: 99%